Slapstick Encyclopedia - Vol. 5 & 6 Keaton, Arbuckle and St. John ; Hal Roach's All-Star Comedians - Arbuckle, Fatty; Jeske, George; Roach, Hal; MacCarey, Leo (image Entertainment, 2002)
The clowns of the American silent screen bring laughter to a new generation in this wonderful box set, featuring 53 short films from the era's funniest comic talents: Laurel and Hardy, Fatty Arbuckle, Buster Keaton, Mack Sennett, Charlie Chaplin, Harold Lloyd, Harry Langdon, Will Rogers, Ben Turpin and more. Meticulously prepared for DVD with fresh new musical scores, "Slapstick Encyclopedia" is a unique collection of silent comedy gems. [www.amazon.com]